Care-seeking practices for non-communicable chronic conditions in a low-income neighborhood in Southern India. - Nilanjan Bhor (Public Library of Science (PLoS), 2023)
Background Given that access to healthcare is less challenging in urban India, evidence shows that affordable government healthcare services are underutilized by the vulnerable and disadvantaged groups. There are emerging studies on healthcare seeking behavior in the context of short-term morbidities and communicable diseases that attempted to understand this gap of underutilization of government healthcare services, but similar studies are rare in the context of non-communicable diseases (NCDs) and associated chronic conditions. Given the urban health system is ill- prepared and ill-equipped to deliver NCD services, it is important to understand how the vulnerable and disadvantaged groups seek healthcare for chronic conditions. This article investigates the care-seeking practices of these individuals living in a low-income neighborhood and care-seeking pathways for chronic conditions. Methods The study is conducted at Kadugondanahalli-a low-income neighborhood with the presence of a recognized slum, in Bengaluru city. A total of twenty in-depth interviews are conducted with individuals diagnosed with non-communicable chronic conditions. Participants were selected through purposive and snowball sampling method. The data is collected between January 2020 to June 2021. Results The study participants practice a wide range of care-seeking practices based on the management of comorbidity and multimorbidity, recognizing the symptoms and severity, experiences of family members, belief, and purchase and consumption of medicines. These practices clearly highlighted not only the nuances of non-adherence to the long-term treatment and medications, but it also strongly influences the care-seeking behavior, which in turn make the care-seeking continuum very complex. The care-seeking continuum attempted each of the components (i.e. the screening, diagnosis, treatment, and control) of NCD care cascade but participants often failed to do screening on time, delayed diagnosis, and did not meet the treatment goals, leading to their conditions becoming further uncontrolled due to the care-seeking practices they practice. These practices delayed not only the diagnosis but also the completion of each component of the care cascade. Conclusion This study emphasizes strengthening of the health system in addressing the individual and community level practices, that significantly affect the entire care-seeking continuum, in the sustained monitoring and adherence to the treatment of chronic conditions.